ANALISIS KINERJA KEUANGAN PADA (PDAM) KOTA GORONTALO - Amali, Lanto Miriatin (Jurnal Pelangi Ilmu, 2012)
This research intent for: (a ). analyzed is PDAM'S finance performance Gorontalo's City bases Number Ministry Of Home Affairs decision 47 Years 1999 about financial Performance Estimation guidances PDAM, (b ) analyzed PDAM'S performances Gorontalo's Cities bases finance ratios. In analisis's result PDAM'S finance performance Gorontalo's City points out adverse and inauspicious it can be seen of 10 analisis finance ratio bases KEPMENDAGRI, where 5 among those point out reducing category which is profit ratio to appreciative productive assets performances as big as (17,25), ratio unrealizedding to sell as big as (16,5 ), unrealized ratio hads out before depreciation cost to subject installment and maturity value flower and credit billing duration assess performance as big as (18,75), productive asset ratio to water loan assesses performance as big as (18), and 5 another financial performance ratios point out categories not good namely current asset ratio to smooth book debts, longterm book debt ratio to ekuitas, operational cost ratio to income and billing effectiveness assesses performance as big as (3,75), and assets totaled ratio to full scale performance point book debt as big as (6 ). Mean analisis is performance bases finance ratio point out more optimal, it can be seen from average value of year goes to tend year experience step-up, as Current ratio, quick ratio, inventory turnover, receivable turnover in days, full scale assets turnover and ROE.